INTRUSIVE GRANITOIDS OF THE NORTHERN LADOGA REGION: CHEMISTRY, FLUIDS, AND OXYGEN ISOTOPES - Sedova J.S.; Krylov D.P.; Samorukova L.M.; Hoernes S. (My University, 2001)
Structural and geological data, in combination with rock geochemistry and crystallization parameters, indicate that asynchronous intrusive granitoid complexes in the Northern Ladoga region, which are represented by the Kurkijoki pluton and its satellites, as well as the Lauvatsaari and Tervus plutons, do not belong to a single magmatic series. The study of fluid inclusions and contents of fluid components in minerals show that the ratio of water to carbon dioxide in fluid increased from older enderbitic to younger granitic magmas. The temperature of the equilibrium distribution of oxygen isotopes among minerals decreases in this rock sequence. This variation corresponds to important events in the pluton formation. The oxygen isotopic ratios in fluids, which were calculated for similar temperatures, are identical and may indicate the magma crystallization in a common fluid flow.